Molecular genotyping, diversity studies and high-resolution molecular markers unveiled by microsatellites in Giardia duodenalis - Durigan, Maurício; Cardoso-Silva, Claudio Benício; Ciampi-Guillardi, Maísa; Toledo-Silva, Guilherme; Mori, Gustavo M. [UNESP]; Franco, Regina M. B.; Souza, Anete P. (Public Library of Science (PLoS), 2018)
Background: Giardia duodenalis (synonyms G. lamblia and G. intestinalis) is an enteric protozoan parasite of a wide range of mammalian hosts, including humans and various domestic and wild animals. There is considerable genetic variability in G. duodenalis and isolates of this parasite have been divided into eight genetic assemblages. Microsatellites markers can be used to discriminate isolates with a high level of sensitivity. This study was conducted to identify and characterize genomic microsatellites (simple sequence repeats—SSRs), sequences of one- to six-nucleotide motifs repeated in tandem, present in the available genomes of G. duodenalis and to develop new markers that can serve as a tool for detection and for characterizing the genetic diversity of this parasite. Methodology/ Principal findings: For each genetic assemblage, polymorphism levels for the microsatellite markers were evaluated. After performing the analysis using the MISA and SciRoKo software, 1,853 simple sequence repeats (SSRs) were identified. In all the genomes, trinucleotide repeats were the most common class followed by tetranucleotide. Many of the SSR loci are assemblage-specific, and 36 SSR loci shared among all the genomes were identified. Together with hypothetical proteins, variant-specific surface proteins represented nearly half of the annotated SSR loci. The results regarding the most common repeat among the SSRs led us to infer that positive selection occurred to avoid frameshift mutations. Additionally, based on inter- and intra-genetic assemblages polymorphism analyses, we unveiled previously undetected genetic variation, indicating that the microsatellite markers we developed are useful molecular tools for epidemiological inferences based on population genetics patterns and processes. Conclusions: There is increasing demand for the development of new molecular markers and for the characterization of pathogens at a higher resolution level. In this study, we present 60 G. duodenalis microsatellites markers that exhibited high polymerase chain reaction (PCR) amplification efficiency among the different genetic assemblages. Twenty of these markers presented nucleotide sequence polymorphisms and may be used as a genotyping tool. The monomorphic markers can be used for the detection of the parasite at the species and genetic assemblage level. These polymorphic markers revealed a genetic diversity that was previously undetectable, thus they can be considered valuable molecular tools for high resolution markers in future studies investigating Giardia and may also be used for epidemiological inferences based on populations genetics patterns and processes.